2020
DOI: 10.1021/acs.nanolett.0c02815
|View full text |Cite
|
Sign up to set email alerts
|

Folding a Single-Molecule Junction

Abstract: Stimuli-responsive molecular junctions, where the conductance can be altered by an external perturbation, are an important class of nanoelectronic devices. These have recently attracted interest as large effects can be introduced through exploitation of quantum phenomena. We show here that significant changes in conductance can be attained as a molecule is repeatedly compressed and relaxed, resulting in molecular folding along a flexible fragment and cycling between an anti and a syn conformation. Power spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 47 publications
1
52
0
Order By: Relevance
“…Specifically, in 1-0 where the molecular structure is just formed, a red direct tunneling path between the gold electrode and the molecular backbone, namely, through-space, is found. [34] Similarly, an identical phenomenon is found when the molecule is about to rupture (1-2). On the contrary, only the through-bond path is observed in the stable configuration .…”
Section: Resultsmentioning
confidence: 61%
“…Specifically, in 1-0 where the molecular structure is just formed, a red direct tunneling path between the gold electrode and the molecular backbone, namely, through-space, is found. [34] Similarly, an identical phenomenon is found when the molecule is about to rupture (1-2). On the contrary, only the through-bond path is observed in the stable configuration .…”
Section: Resultsmentioning
confidence: 61%
“…Additionally, this distinction of the resistance scaling of the noise could detect molecular folding, where the folded molecule experienced a parallel through-space current noise between the gathering phenyl rings, which is absent in an unfolded junction. 46 The noise characteristics also deliver fundamental information about two-dimensional devices, like graphene nanogaps 47,48 or graphene single-electron transistors. 49 The former system is exemplified in Fig.…”
Section: Resistance Scaling Of the Noisementioning
confidence: 99%
“…Toward this end, experimental techniques such as scanning tunneling microscopy break junction (STM-BJ) (4) and mechanically controllable break junction (MCBJ) (5) in combination with nonequilibrium Green's function (NEGF) based computations (3) provide a means to capture and analyze electronic charge transport phenomena in molecular junctions. These techniques have demonstrated that molecules can function as wires (6,7), switches (8)(9)(10), rectifiers (11,12), transistors (13), and potentiometers (14). However, for creating functional devices, it is essential to assemble such molecular electronic components on a single scaffold akin to a printed circuit board in conventional electronics.…”
Section: Introductionmentioning
confidence: 99%